Improving Conceptual Knowledge in Elementary School Students with Revised Bloom's Taxonomy-Oriented Learning Activities - Premana, Dewa Nyoman Dede; Widiana, I Wayan; Wibawa, I Made Citra (Universitas Pendidikan Ganesha, 2023)
Lack of planning in implementing learning activities makes learning less attractive, so students cannot follow the lesson properly. This study aimed to develop revised Bloom taxonomy-oriented learning activities to improve the conceptual knowledge skills of fourth-grade elementary school students. This type of research is development research. The subjects in this study involved four lecturers and 37 students. The four lecturers who were the subjects of this research were divided into two experts, namely learning media experts and two content experts. Interviews, document recordings, tests, and questionnaires of the rating scale type. Furthermore, it was analyzed using descriptive and inferential analysis techniques (t-test). The development results show that the activities developed have been declared valid based on the judgment of the experts—the results of testing the effectiveness with the Independent sample t-test. The SPSS 17.0 for windows assisted test shows that the significance (2-tailed) is 0.00 <0.05, so H0 is rejected and H1 is accepted. Thus it can be concluded that learning activities oriented to the Revised Bloom's Taxonomy significantly influence the conceptual knowledge abilities of fourth-grade elementary school students. This research implies that this neatly arranged learning activity can be utilized by teachers to make the learning process more effective.